(3GddGdF GdHGgQI aj CMcGe GdYJQI GdWGgQIs - (3eMeO QVG Hf bGSe Hf eMeO GdZQGhj, J (B1385(3g` (B1965(3es ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg QH GdYGdejf(B... (3gPg YOI aQhY LeYJgG HYO Cf cGfJ efJHPI hLedI eSGFd CdaJgG HYO Cf cGfJ eJaQbI (B... (3ebOeI, hajgG ebGUO YOI, GdebUO GdChd aj aVd GdYdes
(3BNQgG (B:s
(3BNQgG(B: (3eSFdI dCf QLdG Mda Cf jRf ajdG, GdLhGH(B: (3ddfHj dg jONd Gdajd aj GdSajfI Ke jfXQ Edi ehVY eHdZ GdeGA ef GdSajfI ajYde Ydjg Ke jNQL Gdajd (B... (3aEPG HdZ GdPj Yde Ydjg CNQLg hhRfg(B. (3hEdi gfG La eOGO GdCbdGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B6: 128s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3abg GdePGgH GdCNQis